MAKNA SIMBOLIK DAN FUNGSI ULOS MASYARAT BATAK TOBA KABUPATEN SAMOSIR - Rodearni S Rodearni S; Ridwan Melay; Tugiman Tugiman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : Culture is the expression of human ideas, ideas and actions in meeting the needs of everyday life, which is obtained through the process of learning and teaching. The culture conceptually has seven (7) components: Religion, Science, Technology, Economics, Social Organization, Language and Communication and Art. One of the artworks of the Batak Toba ethnic community is "Ulos". Ulos is a symbol of blessing, compassion and unity. Literally, ulos means a blanket that warms the body and protects it from cold air. Ulos type specifically in Toba Batak custom is Marature Star, Ulos Mangiring, Ulos Ragi Hotang, Ulos Sibolang, Ulos Ragi idup. The symbolic meaning of Ulos is there are several types namely: Furnace symbol, Line Symbol, Hotang Symbol, Star Symbol, Symbol Boras starch, Symbol of Gears, Bonang Manalu symbol. Function Ulos: The functions of Ulos Toba Batak customary Samosir District there are some that are Official Clothes In Indigenous Ceremonies based on life cycles such as At weddings, Birth Ceremonies, Death Ceremonies and Functions Ulos based on importance: As Reply Services To Parents, As Clothing Dancers On Adat Dance (Manortor) or performing arts, Ulos in political activities, Ulos in socio-culture. Samosir regency is the majority of Batak tribe, every event custom is inseparable from Ulos cloth. This Ulos cloth has the function and symbolic meaning of Ulos from every custom event.Keywords: Type, Symbolic Meaning, Ulos Toba Batak Toba, Samosir District.